The potential role of dietary calcium in obesity - Cummings, Nicola Kim (Curtin University, 2006)
There is substantial evidence from cellular, animal and epidemiological studies in support of a role for calcium, and in particular, dairy foods in the regulation of weight (McCarron, 1983; Davies et al. 2000; Heaney, 2003a; Jacqmain et al. 2003; Parikh & Yanovski, 2003; Soares et al. 2004a; Azadbakht et al. 2005). These studies suggest, but do not provide, a causal link between increased calcium intake and reduced adiposity. In contrast, randomised controlled trails (RCT) are limited and their outcomes, to date, are conflicting in their findings (Zemel et al. 2004b; Harvey-Berino et al. 2005; Thompson et al. 2005; Zemel et al. 2005a; 2005b). The primary mechanism involves the control of intracellular calcium by calcitrophic hormones, vitamin D3 and PTH. It is proposed that a higher calcium intake lowers the calcitrophic hormones, thus reducing intracellular calcium and attenuating lipid storage (Zemel et al. 2000). Other flow through effects may include the greater utilisation of fat as a fuel source, increased thermogenesis, increased fat excretion, improved satiety and reduced food intake. (Melanson et al. 2003; Sun & Zemel, 2004; Boon et al. 2005a; Gunther et al. 2005b; Jacobsen et al. 2005b; Melanson et al. 2006). In this thesis we demonstrate that the acute ingestion of calcium, increased postprandial fat oxidation in overweight and obese humans. The results were consistent between the two sources of calcium tested (dairy and calcium citrate). Circulating levels of non-esterified fatty acids (NEFA) were less suppressed, while glycerol tended to be higher following both high calcium meals (Cummings et al. 2006).There was no evidence of a modulation of subjective feelings of hunger, or satiety, nor immediate food intake (buffet) or 24 hour food intake. A prolongation of the inter-meal interval was however observed in subjects consuming the high calcium meals. A single-blind 12 week RCT, with a 12 week wash out period, compared two energy restricted (ER) diets either high (HC 1200 mg/d) or low in calcium (LD 600 mg/d). Forty overweight/obese male and female subjects were recruited for the study with 29 subjects completing both arms of the study. Anthropometric data and body composition from DEXA were measured before, during and following each diet. There was no difference between the diets in the loss of body weight, total fat mass or trunk fat mass. A greater reduction in waist circumference of 1.23 cm was observed when subjects had consumed the HC diet; this however was just short of significance (P=0.052). There was a smaller reduction of resting energy expenditure on the hypocaloric HC diet with a trend for a greater fat oxidation at week 10 of intervention. No differences were observed between the treatment groups for fasting levels of glucose, insulin, Hba1c, LDL-C, HDL-C or TC. We also found an inverse relationship between resting metabolic rate at the start of ER and body fat lost when subjects consumed the LC diet, but not the HC diet.This is a novel finding in that it would be expected to see an inverse relationship between initial RMR and the amount of fat lost; however, the HC diet seems to achieve the same fat loss as the LC diet by taking away the effect of initial body size/composition. Overall, the ingestion of a single meal containing 500 mg of dietary and elemental calcium has some benefits for the obese individual. Six hours post-prandially fat oxidation is stimulated following the consumption of the dietary and elemental calcium breakfast meals. During a 12-week weight loss period, a higher calcium intake did not result in a greater weight loss compared to a low calcium diet. The HC diet did result in a trend for a greater reduction in waist circumference; however, this did not transcribe into an increased loss of total or regional body fat.